2020
DOI: 10.1161/circulationaha.119.042640
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Microvesicles Mediated Pathological Communications Between Dysfunctional Adipocytes and Cardiomyocytes as a Novel Mechanism Exacerbating Ischemia/Reperfusion Injury in Diabetic Mice

Abstract: Background: Diabetes mellitus exacerbates myocardial ischemia/reperfusion (MI/R) injury by incompletely understood mechanisms. Adipocyte dysfunction contributes to remote organ injury. However, the molecular mechanisms linking dysfunctional adipocytes to increased MI/R injury remain unidentified. The current study attempted to clarify whether and how small extracellular vesicles (sEV) may mediate pathological communication between diabetic adipocytes and cardiomyocytes, exacerbating MI/R injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 49 publications
0
86
0
3
Order By: Relevance
“…Diabetic serum exosome injection to the non-diabetic heart caused poorer cardiac function recovery, larger infract size, and increased apoptosis of cardiomyocytes. It was confirmed through various analysis that miRNA-130b-3p was responsible for the cardiotoxicity, and its direct downstream targets were AMPKα1/α2, Birc6, and Ucp3 ( Gan et al, 2020 ). Microglia-derived exosomes were found to mediate neuroinflammation ( Kumar et al, 2017 ) and Alzheimer’s disease propagation ( Saeedi et al, 2019 ).…”
Section: Insight Of Native Exosomes For Strokementioning
confidence: 91%
“…Diabetic serum exosome injection to the non-diabetic heart caused poorer cardiac function recovery, larger infract size, and increased apoptosis of cardiomyocytes. It was confirmed through various analysis that miRNA-130b-3p was responsible for the cardiotoxicity, and its direct downstream targets were AMPKα1/α2, Birc6, and Ucp3 ( Gan et al, 2020 ). Microglia-derived exosomes were found to mediate neuroinflammation ( Kumar et al, 2017 ) and Alzheimer’s disease propagation ( Saeedi et al, 2019 ).…”
Section: Insight Of Native Exosomes For Strokementioning
confidence: 91%
“…The decreased EV microRNA-21-5p derived from heart failure patients impaired cardiac regenerative potential by inhibiting angiogenesis and cardiomyocyte survival [10]. And the enriched miR-130b-3p in dysfunctional adipocyte-derived EV was found by our team mediating diabetes-related cardiac injury through suppression of cardioprotective molecules expression in cardiomyocytes [11]. Therefore, systematical and precise dissection of the myocardium-derived EV moleculars under IH conditions is so important as that will help to determine the main mechanism of OSAS or IH-associated cardiovascular diseases, and subsequently aid to develop more effective and precise diagnosis and treatment in clinical practice.…”
mentioning
confidence: 88%
“…This transfer involves the Ad‐EV cargo miR‐130b‐3p. By acting on downstream targets such as AMPKα1/α2, Birc6, and Ucp3, the transfer of this miRNA leads to deleterious effect on cardiac function, suggesting that small Ad‐EVs act as pro‐deleterious messengers 75 . By contrast, different studies have suggested the beneficial effects of ADSC‐EVs in cardiac recovery, rendering them a great potential for use as therapeutic tools in regenerative therapies 76 .…”
Section: Adipocyte‐derived Extracellular Vesicles Are Involved In Dismentioning
confidence: 99%